Understanding Treatment-resistant Depression: A Missionary's Autobiographical Case Report - Hunter York (Health for All Nations, 2019)
As a career cross-cultural missionary in Southeast Asia, the author has seen first-hand and has personally experienced the devastating effects of colleagues, families, leaders, clinicians, and the sufferers themselves misunderstanding the symptoms and the reality of major depressive disorder, an increasing global health problem. This autobiographical case report reflects on twenty years of treatment-resistant depression and a journey through pharmacological approaches, psychotherapy treatment, Christian prayer counselling, and electro convulsive therapy without improvement in this condition. The primary concern is how to remain faithful and effective with this condition in a service-oriented occupation that requires regular emotional expenditure. In lieu of effective conventional and non-conventional therapies, the remaining option is to find a way to manage chronic depression; identify personal trends, weaknesses, and triggers; and find a personalized way to live that minimizes the effects of the condition. In any chronic, incurable disorder, the sufferer must inevitably come to terms with his or her reality and find peace in the acceptance of that reality. By expressing the journey through treatment-resistant depression, the author encourages readers to persevere in ministry and to respond more appropriately to the afflicted with clearer understanding and empathy. A companion article on mitigating depression symptoms through the spiritual discipline of identifying with Christ and His experience of human emotional pain during His passion is available.